Assessing Current‐Carrying Capacity of Aerosol Jet Printed Conductors. Issue 11 (8th July 2020) - Alhendi, Mohammed; Sivasubramony, Rajesh S.; Weerawarne, Darshana L.; Iannotti, Joseph; Borgesen, Peter; Poliks, Mark D.
Abstract : Printed conductors are the main building blocks of printed flexible electronic circuits. With the advancement and growing demand for printed and flexible electronics, researchers are focused on assessing the mechanical reliability of interconnects. Even more important is, often, the electrical performance or the current‐carrying capacity of the interconnects. A mechanically reliable interconnect has limited use if it cannot meet the current‐carrying requirements. However, current‐carrying capacity curves and circuit design guidelines such as those available for conventional copper conductors have not yet been established for printed interconnects, i.e., there is a technological gap in this domain. The present work focuses on assessing the maximum allowed current through an aerosol jet printed silver nanoparticle‐based conductor on a 75 μm thick polyimide substrate. The temperature coefficient of resistance for the printed ink is experimentally determined. The effect of printed ink microstructure on the temperature coefficient of resistance is also investigated. Standard curves are generated that would guide designers to determine the trace width required for an allowed temperature increase. Furthermore, the effect of sintering temperature on the current‐carrying capability is evaluated. Abstract : Understanding the behavior of additively printed electronics is crucially important to advance their use. A significant number of studies have been published investigating the mechanical performance of printed conductors, but the electrical performance has not been fully addressed yet. This article addresses important aspects related to the electrical performance of aerosol jet printed conductors including current‐carrying capacity and temperature coefficient of resistance.